2020
DOI: 10.1098/rspb.2020.0875
|View full text |Cite
|
Sign up to set email alerts
|

Echolocation call frequency variation in horseshoe bats: molecular basis revealed by comparative transcriptomics

Abstract: Recently diverged taxa with contrasting phenotypes offer opportunities for unravelling the genetic basis of phenotypic variation in nature. Horseshoe bats are a speciose group that exhibit a derived form of high-duty cycle echolocation in which the inner ear is finely tuned to echoes of the narrowband call frequency. Here, by focusing on three recently diverged subspecies of the intermediate horseshoe bat ( Rhinolophus affinis ) that display divergent echolocation call frequencies, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 82 publications
0
13
2
Order By: Relevance
“…There is increasing evidence that the potassium ion channel encoding gene ( KCNQ4 ), motor protein ( Prestin ) and other key genes involved in the sound signal transduction (i.e., TMC1 , CDH23 , Pcdh15 and Otof ) undergone adaptive evolution in echolocation bats, and were strongly associated with the high-frequency hearing [ 24 , 27 , 55 57 ]. However, these genes exhibited no significant expression difference between the sexes of O. tormota .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that the potassium ion channel encoding gene ( KCNQ4 ), motor protein ( Prestin ) and other key genes involved in the sound signal transduction (i.e., TMC1 , CDH23 , Pcdh15 and Otof ) undergone adaptive evolution in echolocation bats, and were strongly associated with the high-frequency hearing [ 24 , 27 , 55 57 ]. However, these genes exhibited no significant expression difference between the sexes of O. tormota .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent high-throughput RNA-Sequencing (RNA-Seq) technologies provided us a large-scale platform to address the molecular mechanisms underlying the adaptive evolution of particular phenotypes in non-model organisms [ 26 28 ]. For example, Sun et al (2020) found that the expression level of FBXL15 gene played an important role in changing the call frequency of horseshoe bats based on comparative transcriptome analysis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of how they can maintain such divergent and non‐overlapping echolocation frequencies. The answer to this question requires evolutionary development studies to identify the loci which code for echolocation frequency (e.g., Sun et al ( 2020 )) and how these loci are assorted during gamete formation.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of how they can maintain such divergent and non-overlapping echolocation frequencies. The answer to this question requires evolutionary development studies to identify the loci which code for echolocation frequency (e.g., Sun et al (Sun et al , 2020)) and how these loci are assorted during gamete formation.…”
Section: Discussionmentioning
confidence: 99%